Architectural Interaction between Space and Behavior (Case Study: Santika Dyandra Hotel Medan’s Lobby) - Sigit, Faurantia Forlana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Medan is the most tourism town that is in much demand in Indonesia, both from domestic and foreign. The hotel has become an important means to support the activities of tourism or business. Hotel Santika Dyandra Medan is one of the four-star hotels and is quite prestigious, located in the city of Medan. One room that can not be separated from a hotel is the lobby area of the hotel which is the main facility. The interior design of the lobby space is generally focused on aspects of the function. But in its development of interior design has a wider outreach, one of which is an aspect of human behavior as userspace. The interior design of Hotel Santika Dyandra Lobby is closely related to the problem of human activity, which is like conducting the check-in, check-out, or just sit in the lobby lounge. There are three elements of a major factor in the design of the interior, namely human, space, and environment. This study aimed to determine whether human behavior shaping the function of Hotel Santika Lobby space or otherwise, by using the theory of behavior settings. This can be analyzed through a pattern of activity that formed on each mapping, where each pattern follows the application form from the lobby area itself, as well as the arrangement of the various furniture.